Circumcision does not have effect on premature ejaculation: A systematic review and meta‐analysis. (27th June 2017) - Yang, Y.; Wang, X.; Bai, Y.; Han, P.
Summary: We attempted to evaluate whether circumcision has an effect on premature ejaculation. We searched three databases: PubMed, EMBASE and Google scholar on 1 May 2016 for eligible studies that referred to male sexual function after circumcision. No language restrictions were imposed. The Cochrane Collaboration's RevMan 5.2 software was employed for data analysis, and the fixed or the random‐effect model was selected depending on the heterogeneity. Twelve studies were included in the meta‐analysis, containing a total of 10019 circumcised and 11570 uncircumcised men. All studies were divided into five subgroups by types of study design to evaluate the effect of circumcision on premature ejaculation (PE). Intravaginal ejaculation latency time (IELT), difficulty of orgasm, erectile dysfunction (ED) and pain during intercourse were also assessed because PE was usually discussed along with these subjects. There were no significant differences in PE (odds ratio [OR], 0.90; 95% confidence interval (CI), 0.72‐1.13; p  =   .37) and orgasm (OR, 1.04; 95% CI, 0.89‐1.21; p  =   .65) between circumcised and uncircumcised group. However, IELT (OR, 0.72; 95% CI, 0.60‐0.83; p  < .00001), ED (OR, 0.42;95% CI, 0.22‐0.78; p  =   .40) and pain during intercourse (OR, 0.36; 95% CI, 0.17‐0.76; p  =   .007) favoured circumcised group. Based on these findings, circumcision does not have effect on PE.